Efficacy of Methocarbamol for Acute Pain Management in Young Adults With Traumatic Rib Fractures. Issue 6 (June 2021) - Deloney, Lindsay P.; Smith Condeni, Melanie; Carter, Cassandra; Privette, Alicia; Leon, Stuart; Eriksson, Evert A.
Background: Rib fractures account for more than one-third of blunt thoracic injuries and are associated with serious complications. Use of nonopioid adjunctive agents such as methocarbamol for pain control has increased considerably. Objective: This study aimed to assess the impact of methocarbamol addition to the pain control regimen on daily opioid requirements for young adults with rib fractures. Methods: This observational, retrospective study included patients aged 18 to 39 years with 3 or more rib fractures who were admitted to a level 1 trauma center between July 2014 and July 2018. Patients were dichotomized based on admission before and after methocarbamol addition to the institutional rib fracture protocol. The primary outcome was to determine the impact of methocarbamol on daily opioid requirements. Secondary outcomes included hospital length of stay (LOS) and diagnosis of pneumonia. Results: A total of 50 patients were included, with 22 and 28 patients in the preprotocol and postprotocol groups, respectively. All patients in the latter group received methocarbamol, whereas no patient in the preprotocol group received methocarbamol. Cumulative opioid exposure was significantly less for patients admitted after methocarbamol addition to the protocol (219 vs 337 mg oral morphine equivalents; P = 0.01), and hospital LOS was also decreased (4 vs 3 days; P = 0.03). No significant differences in the incidence of pneumonia or adverse effects were observed. Conclusion and Relevance: This is the first study to evaluate the impact of methocarbamol on reducing opioid requirements. Given the risks associated with opioids, use of methocarbamol as an analgesia-optimizing, opioid-sparing multimodal agent may be reasonable.